1999
DOI: 10.1007/s002130051102
|View full text |Cite
|
Sign up to set email alerts
|

Systemic sulpiride in young adult volunteers simulates the profile of cognitive deficits in Parkinson's disease

Abstract: All of the tasks impaired following sulpiride are known to be sensitive to frontal lobe damage and the precise pattern of deficits seen is consistent with the anatomical distribution of central dopamine receptors. The results are discussed with particular reference to their close simulation of the impairments seen in idiopathic Parkinson's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
171
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(189 citation statements)
references
References 48 publications
14
171
3
Order By: Relevance
“…In particular, TYR depletion increased plasma prolactin and diminished performance on the spatial recognition memory both of which are consistent with lowered DA neurotransmission (Mehta et al, 1999;Harmer et al, 2001). We have previously noted both these effects in healthy male and female volunteers ) and similar effects were apparent in the present group of recovered depressed subjects.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In particular, TYR depletion increased plasma prolactin and diminished performance on the spatial recognition memory both of which are consistent with lowered DA neurotransmission (Mehta et al, 1999;Harmer et al, 2001). We have previously noted both these effects in healthy male and female volunteers ) and similar effects were apparent in the present group of recovered depressed subjects.…”
Section: Discussionsupporting
confidence: 87%
“…More recently, a study using positron emission tomography (PET) demonstrated increased striatal binding of the D 2 receptor ligand, raclopride, after TYR depletion consistent with lowered presynaptic release of DA (Montgomery et al, 2003). Functionally, TYR depletion appears to disrupt basal DA function sufficiently to reduce performance on tasks of spatial recognition memory and spatial working memory , which are sensitive to DA manipulation (Elliott et al, 1997;Mehta et al, 1999). In some but not all studies in healthy volunteers, TYR depletion has been associated with changes in self-rating scales consistent with mildly lowered mood (Leyton et al, 2000;Harmer et al, 2001;McTavish et al, 2001); however, clinical depressive symptomatology has not been described.…”
Section: Introductionmentioning
confidence: 99%
“…Nicotine effects on response inhibition in this study could also be mediated by enhancement of dopaminergic functioning. The dopaminergic system is believed to modulate a range of cognitive processes, including response inhibition (Brozoski et al, 1979;Mehta et al, 1999;Cropley et al, 2006). Both the striatum (especially the caudate) and prefrontal cortex have been identified as regions important for response inhibition (Lawrence et al, 1998;Volkow et al, 1998Volkow et al, , 2004Aron and Poldrack, 2005;Cropley et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Findings in healthy volunteers showed that haloperidol impaired performance in the SWM task (McCartan et al, 2001). Moreover, the D 2 antagonist sulpiride impaired in some (Mehta et al, 1999(Mehta et al, , 2004 but not in all (Mehta et al, 2003(Mehta et al, , 2005) studies working memory performance, while the D 2 receptor agonist bromocriptine enhanced working memory performance in healthy humans (Mehta et al, 2001). In agreement with this finding in humans, systemic administration of the D 2 receptor agonist quinpirole in monkeys influenced working memory performance; while a low dose of quinpirole impaired working memory performance, higher doses led to an enhancement (Arnsten et al, 1995).…”
Section: The Effect Of Haloperidol On Neuropsychological Performancementioning
confidence: 99%